Peningkatan Kemampuan Bermusik Siswa Melalui Pembelajaran Ansambel Campuran di SMA Negeri 3 Kupang - Aristo Wudy, Kristoforus; Juan Sae, Yizrahya; Trivosa Andari Liwu, Ignatia; Dos Santos De Amorlay, Febriana; Imelda Seran, Maria; Ama Ki'i, Oktavianus (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
This Community Service Program (KKN) focused on mixed ensemble training designed to enhance the musical skills of students at SMA Negeri 3 Kupang, East Nusa Tenggara Province. Prior to this program, musical activities at the school had not been well structured due to the absence of a permanent music group that could serve as a platform for students to practice and perform. The main objective of this activity was to establish a school-based mixed ensemble whose members are able to perform music cohesively and harmoniously. The participants consisted of students from SMA Negeri 3 Kupang who demonstrated an interest in music. The training was carried out in three stages: preparation, implementation, and evaluation. The learning methods employed included demonstration and repetitive drills, enabling participants to learn through direct examples and continuous practice. The results of the program showed an improvement in students’ musical abilities, as indicated by the increase in the average score from 2.62 in the pre-test to 4.02 in the post-test. Musical aspects such as notation reading, playing technique, dynamics, tempo, and ensemble cohesion demonstrated substantial improvement. Furthermore, the newly formed ensemble has performed at school events and arts activities in Kupang City. Thus, the KKN program can be considered successful in improving students’ musical skills through mixed ensemble instruction. It is expected that the school will establish the mixed ensemble as a regular extracurricular activity so that students can continue to develop their musical talents and skills.